2017
DOI: 10.1128/jvi.01228-17
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and Simian Immunodeficiency Virus Maintain High Levels of Infectivity in the Complete Absence of Mucin-Type O-Glycosylation

Abstract: A highly conserved threonine near the C terminus of gp120 of human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) was investigated for its contributions to envelope protein function and virion infectivity. When this highly conserved Thr residue was substituted with anything other than serine (the other amino acid that can accept O-glycosylation), the resulting virus was noninfectious. We found that this Thr was critical for the association of gp120 with the virion and that amino acid subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This suggests that the O-glycans might be required for protein-protein interaction (Stone et al 2016). Similarly, in HIV gp120 O-glycosylation of a conserved threonine that is crucial for the association with gp41 has recently been shown to enhance infectivity and incorporation of gp120 into virions, though the virus maintains normal functionality in the absence of the O-glycan (Termini et al 2017).…”
Section: Assembly and Exitmentioning
confidence: 99%
“…This suggests that the O-glycans might be required for protein-protein interaction (Stone et al 2016). Similarly, in HIV gp120 O-glycosylation of a conserved threonine that is crucial for the association with gp41 has recently been shown to enhance infectivity and incorporation of gp120 into virions, though the virus maintains normal functionality in the absence of the O-glycan (Termini et al 2017).…”
Section: Assembly and Exitmentioning
confidence: 99%
“…The O‐glycosite is situated close to a furin cleavage site and has been speculated to play a role in virus assembly. It has, however, been demonstrated that O‐glycosylation is not required for virion assembly or infectivity, but can enhance these processes .…”
Section: Glycosylation Analysis Of Viral Glycoproteinsmentioning
confidence: 99%
“…A similar effect can be achieved using well‐characterized metabolic inhibitors of glycosylation . Such approaches can help determine an overall impact of a certain type of glycosylation on virus function . For example, cell lines defective in glycosyltransferase activity were used for propagation of HSV‐1, showing N‐ and O‐linked glycan maturation is important for virus spread and progeny generation, respectively .…”
Section: Practical Implications Of Glycosite Discovery In Virologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore necessary to employ chemical release methods, such as reductive β-elimination or hydrazinolysis. However, the role of O-glycosylation in Env glycobiology is uncertain and currently there is little supporting evidence for a significant functional or structural role [37]. Studies have previously identified O-glycans on recombinant Env at positions T499 and T606 [13,16,38,39], although a quantitative study also showed that T499 on a native-like trimer mimic was less than 1 % occupied with O-glycans [18].…”
Section: Global Profiling Of the Overall Env Glycosylation Fingerpmentioning
confidence: 99%